PREPARATIONS BASED ON PLANT RAW MATERIALS WITH ANTIBACTERIAL AND FUNGICIDAL ACTION IN DENTISTRY - Велигоря, Ирина; Любченко, Ольга; Полякова, Светлана; Цыганова, Наталия; Иванов, Александр; Сирота, Ольга; Пушкарь, Людмила (SWorldJournal, 2022)
The antimicrobial and fungicidal effect of preparations based on plant materials (a preparation containing fir oil and oak bark extract, and a combined preparation based on Phytor) was studied in comparison with a preparation based on 0.3% chlorhexidine b